Legal Protection for Workers with Fixed-Term Employment Agreements Before and After the Job Creation Law - Hanifah, Ida; Koto, Ismail (Kosmik Hukum, 2025)
Workers perceive that several new provisions regarding Fixed-Term Employment Agreements are detrimental to their rights. According to research findings, an agreement is considered valid if it meets the provisions stipulated in Article 1320 of the Civil Code. The requirements for a valid agreement are regulated in Article 1320 of the Civil Code. Article 1 Paragraph (14) of Law Number 13 of 2003 concerning employment, an employment agreement is: "An agreement between workers/laborers and employers or employers containing work conditions, rights and obligations of the parties." Employment agreements are divided into Fixed-Term Employment agreements and permanent employment agreements. The provisions regarding employment agreements made in writing have been regulated in Article 54, paragraph 1 of Law Number 13 of 2003 on Manpower. The provisions, nature, and type of work for a fixed-term employment agreement can be seen in Article 59. Changes in the duration of Fixed-Term Employment Agreements are regulated in Article 59, Paragraph (4) of the Manpower Law, which states that a Fixed-Term Employment Agreement can be made for a maximum period of two years and may be extended only once for a maximum period of one year. This means that if an employer applies a renewal system, the maximum duration for a Fixed-Term Employment Agreement is four years. However, in Article 81, Number 12 of the Job Creation Law, which amends Article 56 of the Manpower Law, Paragraph (3) stipulates that the employment contract determines the duration of a Fixed-Term Employment Agreement. Article 59 of the Job Creation Law eliminates the specific duration requirement for Fixed-Term Employment Agreements.